2015
DOI: 10.1001/jama.2015.16535
|View full text |Cite|
|
Sign up to set email alerts
|

Management of Graves Disease

Abstract: Management of Graves disease includes treatment with antithyroid drugs, RAI, or thyroidectomy. The optimal approach depends on patient preference and specific patient clinical features such as age, history of arrhythmia or ischemic heart disease, size of goiter, and severity of thyrotoxicosis. Physicians should be familiar with the advantages and disadvantages of each therapy to best counsel their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
222
0
21

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(287 citation statements)
references
References 100 publications
8
222
0
21
Order By: Relevance
“…Sin embargo, los datos de otro centro terciario de referencia mostraron una menor frecuencia de casos severos que lo encontrado en nuestro centro 12 . Las distintas alternativas terapéuticas para la EBG han demostrado una efectividad similar 13,14 , pero presentan algunas diferencias respecto a beneficios en escenarios clínicos particulares y la posibilidad de presentar efectos adversos 15,16 . Los FAT permiten un buen control del hipertiroidismo, pero luego de su suspensión presentan un mayor riesgo de recurrencia con respecto a las otras alternativas terapéuticas 14 .…”
Section: Discussionunclassified
“…Sin embargo, los datos de otro centro terciario de referencia mostraron una menor frecuencia de casos severos que lo encontrado en nuestro centro 12 . Las distintas alternativas terapéuticas para la EBG han demostrado una efectividad similar 13,14 , pero presentan algunas diferencias respecto a beneficios en escenarios clínicos particulares y la posibilidad de presentar efectos adversos 15,16 . Los FAT permiten un buen control del hipertiroidismo, pero luego de su suspensión presentan un mayor riesgo de recurrencia con respecto a las otras alternativas terapéuticas 14 .…”
Section: Discussionunclassified
“…It has been found that some normal physiological processes in females such as pregnancy play a role in elevating levels of total T4 and total T3 (Teti et al, 2016). On the other hand, the autoimmune ailment called Grave's disease induces thyroid gland to produce excessive amount of thyroid hormone which is reckoned a vast common factor for evolution of hyperthyroidism (Brent, 2008, Burch andCooper, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Current treatment of hyperthyroidism includes pharmacotherapy, radioisotope therapy, and surgical treatment [3]. Pharmacotherapy is an important therapy, which includes thiamazole and propylthiouracil (PTU) [1].…”
Section: Introductionmentioning
confidence: 99%